Application of Töplitz matrices to neutron noise diagnostics of the IBR-2M pulsed reactor. (September 2020) - Korepanova, N.V.; Pepelyshev, Yu.N.; Tkachenko, I.M.; Verdú, G.
Abstract: Ensuring the safe operation of nuclear reactors is one of the most significant tasks of nuclear power engineering. The difficulty lies in the necessity of using nondestructive methods. One of such promising methods is the neutron noise diagnostics of a nuclear reactor. In this paper, the possibility of noise diagnostics by the method of positive definite Töplitz correlation matrices is studied. The advantage of this method is its purely mathematical nature; no model of the process is employed. The method is applicable whenever the process is quasi-stochastic. The results are compared with those from the conventional spectral analysis. Highlights: Model-free method based on the properties of positive definite Töplitz correlation matrices. Method of evaluation of the process instability and determination of its frequencies. Method has been applied to the analysis of the IBR-2M pulse reactor noise. Method has been tested both on static and dynamic states of the reactor. Graphical abstract: